Transformations to Open Market Operations : Developing Countries and Emerging Markets. (Economic Issues; Economic Issues ;, 1997)
Open market operations are the major instruments of monetary control in industrial countries and are becoming important in developing countriesand countries in transition. This paper shows how open market operationsare related to other monetary instruments, discusses the role of the market and of the central bank, and takes a brief, practical look at howopen market operations are actually conducted.